2020
DOI: 10.3390/app10165406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tilting Pad Journal Bearing Design Parameters on the Pad-Pivot Friction and Nonlinear Rotordynamic Bifurcations

Abstract: This study numerically analyzes and investigates the effects of the bearing design parameters of a tilting pad journal bearing (TPJB) on the pad-pivot friction-induced nonlinear rotordynamic phenomena and bifurcations. The bearing parameters were set to the pad preload, pivot offset, spherical pivot radius, and bearing length to diameter (L/D) ratio. The Stribeck curve model (SCM) model was applied at the contact surface between the pad and the pivot, which varied to the boundary-mixed-fluid friction state dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Bearing performance is improved by optimizing bearing structural parameters such as tile wrap angle [10] , aspect ratio [11] , bearing clearance [12] , pivot position [13] and pivot flexibility [14][15] [16] . Over the years, a large number of theoretical and experimental studies have provided an important assessment basis for the design and reliability application of tilting pad bearings, forming a common knowledge support [8] [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Bearing performance is improved by optimizing bearing structural parameters such as tile wrap angle [10] , aspect ratio [11] , bearing clearance [12] , pivot position [13] and pivot flexibility [14][15] [16] . Over the years, a large number of theoretical and experimental studies have provided an important assessment basis for the design and reliability application of tilting pad bearings, forming a common knowledge support [8] [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al 30 explored the pivot stiffness effect on the dynamic response of horizontal and vertical rotors supported on TPJBs. Kim et al 31,32 analyzed the nonlinear rotordynamic response of TPJBs considering pad-pivot friction forces. Rendl et al 33 presented a nonlinear dynamic analysis of a four-pad TPJB in load-between-pads (LBP) configuration, supported on flexible pivots.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [15] showed that varying bearing loads, the pivot friction could result in non-synchronous pad tilting and journal vibrations. Kim et al [16,17] focused on the pad-pivot friction-induced nonlinear rotor dynamic phenomena and bifurcations. The Stribeck curve model was applied for friction.…”
Section: Introductionmentioning
confidence: 99%